2014
DOI: 10.1073/pnas.1321652111
|View full text |Cite
|
Sign up to set email alerts
|

Global evaluation of biofuel potential from microalgae

Abstract: In the current literature, the life cycle, technoeconomic, and resource assessments of microalgae-based biofuel production systems have relied on growth models extrapolated from laboratory-scale data, leading to a large uncertainty in results. This type of simplistic growth modeling overestimates productivity potential and fails to incorporate biological effects, geographical location, or cultivation architecture. This study uses a large-scale, validated, outdoor photobioreactor microalgae growth model based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(155 citation statements)
references
References 37 publications
3
148
0
4
Order By: Relevance
“…High variability results in increased infrastructure which would create further operation costs. A study of the global biofuel potential from microalgae by Moody et al (2014) showed the western Kenyan city of Kisumu to maintain an average annual temperature close to the optimum and would therefore be able to maintain high biomass yields; making it an ideal location for microalgae cultivation (Moody et al, 2014).…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…High variability results in increased infrastructure which would create further operation costs. A study of the global biofuel potential from microalgae by Moody et al (2014) showed the western Kenyan city of Kisumu to maintain an average annual temperature close to the optimum and would therefore be able to maintain high biomass yields; making it an ideal location for microalgae cultivation (Moody et al, 2014).…”
Section: Temperaturementioning
confidence: 99%
“…A study carried out by Moody et al (2014) used largescale, validated, outdoor photobioreactor microalgae growth model based on 21 reactor-and species-specific inputs to model the growth of Nannochloropsis. The model accurately accounts for biological effects such as nutrient uptake, respiration, and temperature and uses hourly historical meteorological data to determine the current global productivity potential.…”
Section: Theoretical Maximum Annual Average Lipid Yieldsmentioning
confidence: 99%
“…Microalgae represent an alternative to land plants, since cultures could be developed in non-arable land, employing brackish, saline or even waste water, as well as carbon dioxide from flue gases as carbon source. Values for expected fuel productivity around 20,000 L per hectare and year seem reasonable for outdoor culture of microalgae (Moody et al 2014), although some substantially higher projections are frequently argued in the literature. However, most of the projected values originate from gross extrapolations, both in area and time, from short-term trials in small size facilities, if not directly from laboratory experiments.…”
Section: Biofuel From Microalgae?mentioning
confidence: 94%
“…Algae hold much promise as a viable feedstock for biofuels but there is still much discussion over how to make production more cost effective [1][2][3][4][5][6][7]. High biomass and lipid yields are achievable from algae cultured under controlled laboratory conditions at the bench scale or in incubators (e.g., photobioreactors).…”
Section: Introductionmentioning
confidence: 99%